Statistical Analysis and Inter- Comparison of Solar UV and Global Radiation for Athalassa and Larnaca,Cyprus. - Pashiardis, Stelios; Kalogirou, Soteris A.; Pelengaris, A. (My University, 2017)
A statistical analysis and inter-comparison of the Ultraviolet Radiation (UVR) at two sites in Cyprus representing two different climate regimes of the island (Athalassa-inland plain vs Larnaca-coastal location) covering the period 2013-2015 is presented. Mean annual and mean monthly daily totals of the UV irradiation and their frequency distribution at both sites are computed and discussed. The total accumulated UV irradiation along an average year reaches 398 MJ m-2 at Athalassa and 494 MJ m-2 at Larnaca. During summer, the daily UV radiation exceeds the value of 1800 kJ m-2 at Athalassa and 2200 kJ m-2 at Larnaca. Linear relationships were established between UVR and global solar radiation, with the coefficient of determination close to 1. These relationships indicate that UV irradiation corresponds to 5.9% and 6.8% of the horizontal global solar irradiation at the two sites, respectively. Four models were tested for the estimation of UVR and the best performed models were recalibrated according to the local conditions. Relationships between the clearness index ( kt ) and the UV hemispherical transmittance ( ktUV ) were also established. The annual ktUV is about 71% of kt . Finally, the dependence of the UV/G ratio values to the solar elevation angle and clearness index was also examined. It can be concluded that the presence of clouds reduces less the UV component rather than the global solar radiation, due to the strong absorption of water in the near infrared spectrum.
Keywords: UV irradiance; Statistical analysis; Global clearness index; Ultraviolet clearness index; Modelling; Statistical relationships; Cyprus